Cell uptake, intracellular distribution, fate and reactive oxygen species generation of polymer brush engineered CeO2-x NPs - Qiu, Yuan; Rojas, Elena; Murray, Richard A.; Irigoyen, Joseba; Gregurec, Danijela; Castro-Hartmann, Pablo; Fledderman, Jana; Estrela-Lopis, Irina; Donath, Edwin; Moya, Sergio E. (Nanoscale, 2015)
Cerium Oxide nanoparticles (CeO2-x NPs) are modified with polymer brushes of negatively charged poly (3-sulfopropylmethacrylate) (PSPM) and positively charged poly (2-(methacryloyloxy)ethyl-trimethylammonium chloride) (PMETAC) by Atom Transfer Radical Polymerisation (ATRP). CeO2-x NPs are fluorescently labelled by covalently attaching Alexa Fluor® 488/Fluorescein isothiocyanate to the NP surface prior to polymerisation. Cell uptake, intracellular distribution and the impact on the generation of intracellular Reactive Oxygen Species (ROS) with respect to CeO2-x NPs are studied by means of Raman Confocal Microscopy (CRM), Transmission Electron Microscopy (TEM) and Inductively Coupled Plasma Mass Spectroscopy (ICP-MS). PSPM and PMETAC coated CeO2-x NPs show slower and less uptake compared to uncoated Brush modified NPs display a higher degree of co-localisation with cell endosomes and lysosomes after 24 h of incubation. They also show higher co-localisation with lipid bodies when compared to unmodified CeO2-x NPs. The brush coating does not prevent CeO2-x NPs from displaying antioxidant properties. This journal is
CRIS-Team Scopus Importer:2020-10-13